Linear mapping between magnetic susceptibility and entanglement in conventional and exotic one-dimensional superfluids - Arisa, D. [UNESP]; Franca, V. V. [UNESP] (Amer Physical Soc, 2020)
We investigate the mapping between magnetic susceptibility and entanglement in the metallic, insulating, conventional, and exotic polarized superfluid phases of one-dimensional fermionic lattice systems as described by the Hubbard model. Motivated by recent proposals for determining and quantifying entanglement via magnetic susceptibility measurements, we numerically study the intrinsic relationship between the two quantities at zero temperature. We find signatures of the metal-insulator transition and of the BCS-BEC crossover, but the most relevant result is that for conventional and exotic superfluids the mapping between magnetic susceptibility and entanglement is surprisingly simple: Directly proportional. This linear behavior is found to be universal for conventional superfluids and therefore could be exploited to quantify entanglement in current cold-atom and condensed-matter experiments.